IMPLEMENTATION OF PENAL MEDIATION IN THE PERSPECTIVE OF PROGRESSIVE LAW (STUDY AT THE SEMARANG CITY POLICE DEPARTMENT) - Sri Hartanto; Indah Sri Utari; Ridwan Arifin (Indonesian Journal of Criminal Law Studies, 2019)
Criminal Law has the characteristics of a double-edged sword, because on one side it protects the victim but on the other side deprives the rights of the perpetrators. Therefore, the settlement of cases through criminal lines becomes ultimum remidium because Criminal Law is used as a last resort in solving criminal cases. One form that emerges today is the Penal Mediation effort which is used as a form of settlement of criminal cases, especially for insignificant crimes. The paper analyzes and looks deeper into the implementation of penal mediation at the Police level, in the Semarang City Police Department. The research uses an empirical juridical method with a research location in the city of Semarang. The research underlines that in the implementation of media penalties at the police level is carried out through a Progressive Law framework. In its implementation, the police must base on the principle of conflict resolution, process-oriented, and the process is informal. One of the penal mediation forms implemented and applied by Semarang City Police Department is on domestic violence cases, where the principle that is put forward is Victim Offender Mediation. This study concludes that the implementation of media penal is one form of restorative justice in Indonesia.